Sociodemographic and clinical factors associated with early childhood caries in Peruvian pre-schoolers - Daniel José Blanco-Victorio; Nieves Asteria López-Luján; Walter Bernaola-Silva; Luis Antonio Vicuña-Huaqui; Rocio Cacñahuaray-Palomino; Julissa Sarai Diaz-Campos; Yeni Araceli Anicama-Barrios; Zenaida Rojas-Apaza; Sara Castañeda-Sarmiento; Evelyn Alvarez Vidigal; Roxana Patricia López-Ramos (BMC Oral Health)
Abstract Background Early childhood caries (ECC) is a highly prevalent oral disease among children worldwide, arising from multiple contributing factors. This study aimed to investigate the sociodemographic and clinical factors associated with ECC in preschool children attending a hospital in Ica, Peru. Methods This observational cross-sectional study involved 186 children evaluated during two dental health campaigns organised by a hospital in Ica, Peru. Oral examinations were conducted by two trained paediatric dentists, while haemoglobin levels were measured by two nurses. Mothers or caregivers completed questionnaires to provide relevant sociodemographic and behavioural data. Multiple logistic regression analyses were conducted to identify variables significantly associated with ECC (p < 0.05). The maximum likelihood method was used to assess the contribution of demographic, clinical and other factors—such as oral hygiene and cariogenic diet—using odds ratios (ORs) and regression coefficients to indicate the magnitude and direction of their effects. Results The prevalence of ECC was 76.88%. Among the children, 50.54% were male, with a mean age of 4.44 ± 0.87 years. Most participants had poor oral hygiene (63.98%), while 82.26% of children with anaemia had reduced haemoglobin levels. The mean monthly family income was USD 376.35 ± 168.96. Mothers or caregivers reported brushing their children’s teeth twice daily (56.99%) and giving sweets one to two times daily (79.03%). Factors significantly associated with ECC included the child’s age (OR = 3.32; 95% CI, 1.68–6.58), haemoglobin level (OR = 0.43; 95% CI, 0.25–0.72), monthly family income (OR = 0.99; 95% CI, 0.9972–0.9998) and mother/caregiver education (OR = 0.13; 95% CI, 0.03–0.52). Additionally, dental brushing frequency (OR = 0.13; 95% CI, 0.02–0.65) and sweet consumption (OR = 4.98; 95% CI, 1.05–23.56) were identified as associated behaviours. Conclusion The findings demonstrate that ECC is associated with a child’s age, monthly family income, mother/caregiver education level, haemoglobin level, brushing frequency and sweet consumption.